PERLINDUNGAN HUKUM TERHADAP DOKTER YANG MELAKUKAN PRAKTEK MEDIS MENYEBABKAN PASIEN MENINGGAL DUNIA - Samuel Nainggolan; Ajeng Hanum Arditha Anggraeni; Jamalum Sinambela; Atika Sunarto; Istislam Istislam (Realism: Law Review, 2023)
Doctors are a noble profession. Doctors provide services to patients in the health sector with the aim of recovering from their illness. Doctors in carrying out their practice are guided by all the regulations that function in providing legal protection to themselves. Doctors do their best to seek health for patients regardless of the results. Sometimes the patient does not accept all medical actions performed by the doctor where the patient feels aggrieved. Especially if the patient dies, often the patient's family blames the doctor who treated the patient by saying that the doctor has committed medical malpractice. Therefore we need a legal certainty that regulates medical practice carried out by doctors in order to provide justice and legal protection for doctors in carrying out their duties.